Pengaruh Tax Avoidance dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Farmasi yang terhadap di Bursa Efek Indonesia - Al Lutfie Rizqi Adha Ritonga; Rezki Zurriah (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
This study aims to determine the effect of tax avoidance and profitability on value value in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This research is a type of associative research. The sampling technique was carried out using a purposive sampling technique. So that the sample obtained is 7 pharmaceutical companies on the IDX in 2017-2021 with a total of 35 observational data for 5 years of observation. The data collection technique used is documentation. The data analysis technique used in this study is multiple linear regression analysis with SPSS 24 software tools. The results of the tax avoidance research show that the t-test statistic value of 1.458 is smaller than t-table of 2.034, while the significant value of tax avoidance is 0.155, which is greater than 0.05, this shows that tax avoidance has no effect on firm value. Profitability shows the statistical test value of tcount of 5.988 is greater than ttable of 2.034 while the significant value of profitability of 0.000 is smaller than 0.05, this indicates that profitability has a positive and significant effect on firm value. The results of the research on tax avoidance and profitability together show that the F-count statistic value of 18.572 is greater than the F-table value of 3.29. While the significant value of 0.000 is smaller than 0.05, this indicates that there is a significant influence between tax avoidance and profitability on firm value simultaneously.